2013
DOI: 10.5137/1019-5149.jtn.8176-13.1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and anesthesiological considerations of awake craniotomy: cerrahpasa experience

Abstract: AIm: Awake craniotomy (AC) with electrical cortical stimulation has become popular during the last ten years although the basic principles were introduced almost 50 years ago. The aim of this paper is to share with the readers our experience in 25 patients who underwent AC with electrical stimulation. mATERIAl and mEThods: Twenty-five patients who underwent AC between 2010 and 2013 are the subjects of this paper. All patients were diagnosed with intraaxial lesions involving the functional area itself or very c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Data of the study characteristics are shown in Table 1 . A total of fourteen case series [ 10 , 17 , 19 , 20 , 23 , 28 , 39 , 41 , 44 , 47 , 51 , 53 , 54 , 60 ] thirteen prospective studies [ 18 , 21 , 22 , 25 27 , 30 , 33 , 35 , 38 , 52 , 55 , 61 ], seventeen retrospective studies [ 24 , 29 , 31 , 34 , 37 , 40 , 42 , 43 , 45 , 46 , 48 50 , 57 59 , 62 ], two RCTs [ 32 , 56 ], and one pseudo-RCT [ 36 ] comprising 5945 AC procedures in 5931 patients were analysed ( Table 1 ). Of note, during the data extraction process it appeared that nine studies [ 20 , 22 , 27 , 31 , 42 46 ] partially repor...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data of the study characteristics are shown in Table 1 . A total of fourteen case series [ 10 , 17 , 19 , 20 , 23 , 28 , 39 , 41 , 44 , 47 , 51 , 53 , 54 , 60 ] thirteen prospective studies [ 18 , 21 , 22 , 25 27 , 30 , 33 , 35 , 38 , 52 , 55 , 61 ], seventeen retrospective studies [ 24 , 29 , 31 , 34 , 37 , 40 , 42 , 43 , 45 , 46 , 48 50 , 57 59 , 62 ], two RCTs [ 32 , 56 ], and one pseudo-RCT [ 36 ] comprising 5945 AC procedures in 5931 patients were analysed ( Table 1 ). Of note, during the data extraction process it appeared that nine studies [ 20 , 22 , 27 , 31 , 42 46 ] partially repor...…”
Section: Resultsmentioning
confidence: 99%
“…We divided the identified records into three subtopics according to the used anaesthetic technique: Nineteen studies reported the asleep-awake-asleep (SAS) respectively sleep-awake (SA) technique [ 20 – 23 , 25 27 , 37 39 , 44 46 , 50 , 51 , 53 , 56 , 57 , 60 ], twenty-eight reported monitored anaesthesia care (MAC) [ 10 , 17 19 , 24 , 28 32 , 34 36 , 40 – 43 , 47 49 , 52 , 54 , 55 , 58 62 ] and one used the awake-awake-awake (AAA) technique [ 33 ]. Of note, Souter et al have used the SAS as well as the MAC technique in their patients [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations